2013
DOI: 10.1177/1049909113502845
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Utilization of an Inpatient Palliative Care Consultation Service in an Urban Public Hospital

Abstract: The increased PCC utilization for immigrants is in contrast to previously reported literature. This increased use may be because access to services in a municipal hospital is not driven by demographic and socioeconomic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The involvement of nurses in palliative care consults could result in earlier and more frequent consults, which has been shown to improve patient care. 1,2 To our knowledge, there are no previous studies published discussing the possibility of using already existing resources (nurses, social workers, case managers) to initiate palliative care consults. There are studies evaluating the development and implementation of triggers in the hospital for early palliative care consultations to improve patient care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of nurses in palliative care consults could result in earlier and more frequent consults, which has been shown to improve patient care. 1,2 To our knowledge, there are no previous studies published discussing the possibility of using already existing resources (nurses, social workers, case managers) to initiate palliative care consults. There are studies evaluating the development and implementation of triggers in the hospital for early palliative care consultations to improve patient care.…”
Section: Discussionmentioning
confidence: 99%
“…When patients have access to palliative care early in their medical course, they have improved symptom management, outcomes more consistent with their goals of care, and in some instances, extended length of life. 1,2 Earlier palliative care consults and integrated case management are associated with costsavings and decreased hospital readmissions. [3][4][5][6] Studies have shown that a multidisciplinary approach to palliative care results in improved outcomes in both acutely and chronically ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by the results of previous studies which found a positive impact of PC interventions on the frequency of DNR orders among terminally ill patients. 10,13,15,17,18…”
Section: Discussionmentioning
confidence: 99%
“…11,12 A number of studies described the relationship between PC interventions for patients dying of cancer and DNR designation. 7,10,[13][14][15][16][17][18] However, to the best of our knowledge, none of these studies explored the relationship between the timing of PC involvement and the timing of DNR orders. The aim of the current study was to investigate the relationship between referral to a hospital-based PC service and its timing and the designation of DNR and its timing for patients dying of cancer in a tertiary care hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, 10 trials recruited mainly cancer patients. Four of the trials were RCTs (Engelhardt et al, 2006; Temel et al, 2010, 2017; Radwany et al, 2014), nine were cohort studies (Rabow et al, 2004; O'Mahony et al, 2010; Lustbader et al, 2011; Sacco et al, 2013; Bailey et al, 2014; Kao et al, 2014; Kerr et al, 2014; Tan et al, 2014; Ferrell et al, 2015), and 13 were cross-sectional studies (Parker-Oliver et al, 2003; Buchanan et al, 2004; Sato et al, 2008; Nakano et al, 2012; De Gendt et al, 2013; Bhatraju et al, 2014; Alsirafy et al, 2015; Chen et al, 2015; Patel et al, 2016; Huang et al, 2017; McDonald et al, 2017; Omondi et al, 2017; Reinhardt et al, 2017).…”
Section: Resultsmentioning
confidence: 99%